I Like The Way You Move: An Empirical Investigation into the Mechanisms Behind First Mover and Follower Strategies - Wolfgang Sofka; Tobias Schmidt (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
There appears to be an ambivalent dimension in innovation strategies: timing. When is an innovation ready for the market or when is the market ready for the innovation? This paper empirically investigates the determinants of a firm?s decision to become a first mover or a follower in innovation strategies. Much of theoretical and empirical work has focused on whether first mover strategies pay off or not. Here we take a different approach by analysing the determinants that lead companies to opt for either a first mover or a follower strategy. One of this paper?s major goals is to distinguish between firm and industry specific effects on this particular strategic choice. We estimate our model using the most recent data from the German innovation survey of 2003. This dataset allows us to identify deliberate followers rather than outstripped first movers. One of our main findings is that firms choosing a first mover strategy operate in industries with intensive knowledge exchange and further leverage this advantage through excellent internal absorptive capacities. Followers, though, compete by way of their operational excellence for streamlining processes and cutting costs. Hence, we argue that neither of these two innovation strategies is per se superior to the other.
Keywords: O32; L10; 330; innovation strategy; first mover; bivariate probit; Innovationsmanagement; Innovationswettbewerb; Markteintritt